Electrodermal energy wave at acupuncture points may be a biomarker of aging - Min Chen; Zhengqin Chen; Qian Liu; Yuwei Pan; Qian Gao; Cangcun Xu; Qincui Zhang; Zhaoqing Xi; Huailiang Zhang (Wolters Kluwer Medknow Publications, 2018)
Objective: The main objective is to study the electrodermal energy wave at some acupuncture points on Chinese people with different ages. Methods: The electrodermal screening device MORA-Super (German) was applied to measure the electrodermal energy at 38 acupuncture points and nonacupuncture points on 3949 candidates. Results: There are five groups, including 17 cases ≤12 year, 41 cases between 13 and 18 years, 722 cases between 19 and 39 years, 2995 cases between 40 and 59 years, and 174 cases ≥60 years. The electrodermal energy of candidates older than 60 years increased significantly compared with other groups (P < 0.01). There is positive correlation between electrodermal energy and age (R = 0.582). Conclusion: The electrodermal energy may become a biomarker of aging.